Quenched nematic criticality separating two superconducting domes in an iron-based superconductor under pressure - Coldea, A; Reiss, P (University of Oxford, 2019)
The data reflect experimental transport and tunnel diode oscillator measurements collected in zero field or in magnetic fields either in Oxford or at the NHMFL Tallahassee Florida. Measurements were performed at different applied pressuresusing a piston pressure cell. The data set contain raw data plotted in Figures of the manuscript arXiv:1902.11276 (https://arxiv.org/abs/1902.11276).